Correlation between two quantum concepts within shape phase transitions in nuclei. (11th January 2021) - Ait El Korchi, S.; Chabab, M.; El Batoul, A.; Lahbas, A.; Oulne, M.
Abstract: The present work consists in studying a correlation that we have observed, for the first time, between two well-known quantum concepts, namely: the Minimal Length (ML) and the Deformation-Dependent Mass (DDM) which are widely used in different fields of physics. This correlation was revealed in transitional nuclei near the Critical Point Symmetries (CPS) X(3) and Z(4) through calculations of their energy spectra, moments of inertia and transition probabilities. Based on this correlation which could be considered as a new signature for CPS, we have found eventual new candidate nuclei for these critical points.